Code Switching and Code Mixing Used by Gitasav in Her Interview on the Indah G Show Video - Hafifah, Sulistiya; Adi, Bambang Trisno; Juliansyah, Juliansyah; Afiyati, Alia (Universitas Pahlawan Tuanku Tambusai, 2024)
The aim of the research entitled Code Switching and Code Mixing Used by Gitasav on Her Interview in the Indah G Show Video is to identify the types of code switching and code mixing used by GitaSav. There are three types of code switching, they are Intra-Sentential Switching, Inter-Sentential Switching, and Tag switching. Then for Code Mixing there are three types, namely Insertion, Alternation, and Congruen Lexicalization. In addition, this research seeks to find out what type is most often used by Gitasav in her speech. As a descriptive and qualitative research, the data was collected from the utterances spoken by GitaSav in an interview video uploaded on the YouTube channel The Indah G Show. Out of 37 data found for code switching, intra-sentential is the type most widely used by Gita Sav, whereas from all 21 data found for code mixing, insertion was the most frequently used type.